Smart Cosmetics Suitcase Terkendali Smart Phone - Riska Robianto (Riset Sinergi Indonesia (RISINDO), 2022)
This final project aims to create a technology in the world of beauty, by using the Arduino Mega2560 microcontroller as the controlling brain of the cosmetic suitcase. Arduino is controlled using an Android Smartphone that is connected to the system on the cosmetic suitcase by means of a Bluetooth module as a connecting medium between the cosmetic suitcase and the Android smartphone, the user can control 3 LEDs and the fan by pressing the ON button to turn on and the OFF button to deactivate. Fingerprint functions as a fingerprint scanner to unlock the cosmetic case. This automatic unlocking works based on the logic in the program by using a fingerprint sensor that functions as a fingerprint scanner which then Arduino will instruct the solenoid and buzzer to be active for 5 seconds when the detected fingerprint is registered. Push Button functions as a new fingerprint registrar and as a fingerprint eraser that has been previously registered. Pressing the push button once to register a new fingerprint and pressing the push button for more than 1 second to delete all fingerprints that have been previously registered. LCD serves as an information display. From the results of the research conducted, it was found that this tool is able to help women and MUA to have all the make-up equipment as well as supporting tools such as lighting and fans in a cosmetic suitcase that can be controlled via a smartphone.